Il motivo dei viaggi nell’autobiografia di Vittorio Alfieri - Madarász, Imre (Verbum – Analecta Neolatina, 2019)
Vittario Alfieri was one of the greatest poets and autobiographers, and also one of the greatest travellers of the 18th century, during what we consider to be the period of great voyages (and the era of philosophical empiricism). The many long journeys of Alfieri through Europe, reported in his autobiographical work Vita, are a series of mad flights (using the terminology of Dante, “folli voli”), reflecting a restless soul in search of himself. These journeys never brought the satisfaction of going, there was also the suffering of remaining next to the possibilities of gathering experiences of the world. Landscapes prepared him for his protoromantic poetic works, while the political ones matured him for his strong revolt against tyranny. His consciousness showed a mission of a judge writer (”scrittore tribuno”), a bard of freedom, and his categorical refusal of any type of absolute power, and an admiration for the parliamentary government of a “happy England”.